An analysis of the French strategy in the Indo-Pacific. (2nd January 2021) - Karambelkar, Amruta
ABSTRACT: France has emerged as a country with ambitions in the Indo-Pacific. It has vast territories, population and economic interests in the Indo-Pacific which necessitate a coherent national security policy towards this region. Even before the promulgation of its Indo-Pacific strategy, France has been involved in maritime Asia, primarily through defence sales. The changing balance of power has renewed European attention towards the Indo-Pacific wherein France is making its mark. This article studies the drivers of the French Indo-Pacific strategy and goes further to understand the fundamentals that have led to French attention to this region. A careful study of all major French policy articles lays out the strategic thinking in Paris. The article briefly presents bilateral and multilateral engagements of France. While traditional and non-traditional security issues and normative drive are apparent in the public discourse, it is clear that the major drivers are France's military–industrial complex and the desire to be able to influence the regional order.